1992
DOI: 10.1002/pen.760321809
|View full text |Cite
|
Sign up to set email alerts
|

The yield strength of particulate reinforced thermoplastic composites

Abstract: The effects of the filler volume fraction and strength of adhesion on the mode of tensile failure of a particulate reinforced polypropylene (PP) are investigated using finite element simulation (FES). When there is perfect adhesion between constituents, an upper bound for tensile yield strength is found to be 1.33 times the matrix yield strength above a critical volume of particulate concentration. Utilizing Sjoerdsma's model for interacting stress concentration fields, one can determine the concentration depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 9 publications
(1 reference statement)
1
53
1
Order By: Relevance
“…Recent studies have suggested that the yield behaviour of polymer blends is affected by the interfacial adhesion [31,[33][34]37]. Pukanszky et al [31][32][33][34][35][36][37] have proposed the upper and lower values for the yield stress, in case of extreme values of interfacial adhesion. When the interfacial adhesion is strong enough for the stress transfer to occur between two phases, the yield stress would obey the law of mixtures (the upper value):…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Recent studies have suggested that the yield behaviour of polymer blends is affected by the interfacial adhesion [31,[33][34]37]. Pukanszky et al [31][32][33][34][35][36][37] have proposed the upper and lower values for the yield stress, in case of extreme values of interfacial adhesion. When the interfacial adhesion is strong enough for the stress transfer to occur between two phases, the yield stress would obey the law of mixtures (the upper value):…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The brittle-ductile transition of the composites takes place at filler content of about 4%. According to Percolation Theory [14][15][16][17], this value is defined as the critical volume fraction of this system. At filler content of 5%, the impact strength attains the maximum.…”
Section: Toughness Of Pp/kt Compositesmentioning
confidence: 99%
“…2,3 Unfortunately, the high loading of Al(OH) 3 in PE leads to the reduction of impact strength and elongation at break, due primarily to the poor interfacial adhesion between the two components. Coupling agents act to provide a means of transferring stress from the polymer matrix to the filler particles, which ultimately result in better mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Halogen-based flame retardants were used to produce flame-retardant PE for many years, but they give off heavy smoke and hazardous gases during combustion. In recent years, nonhalogen flame retardants such as Al(OH) 3 and Mg(OH) 2 have therefore been considered an attractive alternative to halogen-based flame retardants and have become a major trend in the development of flame-retardant polyethylene.…”
Section: Introductionmentioning
confidence: 99%